THE EXPORT STRATEGIES AND PERFORMANCE OF SMEs - Comparison between Finnish SMEs in consumer, production, and service sectors - Räsänen, Harri (My University, 2002)
The purpose of the study was to examine the determinants of export performance between Finnish small and medium sized firms in three different sectors. The sectors were consumer, production, and service sector. The export performance was thought to be an outcome of situational variables and export strategies. To achieve its purpose the study also intended to: 1) compare impacts of situational variables on export strategies across sectors; 2) compare impacts of situational variables on export performance across sectors; 3) compare impacts of export strategies on export performance across sectors; 4) examine the concurrent relationship of situational variables and export strategies on export performance; 5) construct a multi-item measure of export performance. Total of 33 hypotheses were developed. A cross-sectional survey was used in the study. The data used consisted of 195 Finnish exporting firms. The export performance was measured with 15 variables. The statistical techniques used were ANOVA, correlation analysis and regression analysis. The results indicated that the situational variables of exporter differed between three sectors under study as determinants of export strategies as well as determinants of export performance. According to impacts of export strategies on export performance the sectors did not differ considerably. Results indicated that there doesn't exist certain export strategies in consumer, production, or service sector that clearly leads to better or worse export performance. Together situational variables and export strategies explained export performance better than either alone. Total of 11 hypotheses were accepted. Most of the results within and between sectors varied to some extent with different measures of export performance. The developed export performance sum variable and multi-item export performance measures were proven to be valuable in the analyses.
Keywords: Export; Performance; Strategy; SME; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|